Enhancing Harmony in Life of Vulnerable Worker Group When Facing the COVID-19 Pandemic - Lanwong, Tanika; Kitrenu, Pattaraporn; Balthip, Karnsunaphat; Nudla, Palida; Phoomchaiya, Sirimas; Suwanruangsri, Sarana (Journal of Research in Nursing-Midwifery and Health Sciences, 2023)
Objective: To understand the process of enhancing harmony in life of vulnerable worker groups when facing the COVID -19 pandemic. Methods: This study followed grounded theory. Data were gathered from 29 participants through in-depth interviews and non-participant observations for 6 months based on the inclusion criteria. Data analysis was guided by Strauss and Corbins grounded theory. Results: The results showed the core category of struggling to survive which reflected the process of enhancing harmony in life of worker vulnerable people facing the COVID-19 pandemic. The results were divided into three categories. Category 1, the conditions, conditions were divided into four sub-categories: 1) having life capital before the pandemic of COVID-19, 2) having connectedness, 3) having groups support, and 4) understanding and accepting the situation that occurred. Category 2, the strategies, strategies used by participants to enhance the harmony in their lives during the COVID-19 pandemic, were divided into five sub-categories: 1) searching for new opportunities and alternative occupations, 2) living life with self-sufficiency and not creating more debt, 3) adopting safe behaviors to avoid contracting COVID-19, 4) seeking a way to relax, and 5) accepting the limitation in life and living a normal life. Category 3, the consequences, consequences impacting the lives of the participants, were divided into four sub-categories: 1) finding self-value and purpose in life, 2) realizing the value of friendship, 3) developing the bonding among family members, and 4) more concern for health. Conclusion: The findings may help in the development of a holistic program and formulation of policies to prepare vulnerable people to be able to live in harmony by promoting purpose in life, selfacceptance and understand and acceptance the truth of life.